Circulating markers of angiogenesis and endotheliopathy in COVID-19. (November 2020) - Pine, Alexander B.; Meizlish, Matthew L.; Goshua, George; Chang, C-Hong; Zhang, Hanming; Bishai, Jason; Bahel, Parveen; Patel, Amisha; Gbyli, Rana; Kwan, Jennifer M.; Won, Christine H.; Price, Christina; et al.
Increase in thrombotic and microvascular complications is emerging to be a key feature of patients with critical illness associated with COVID-19 infection. While endotheliopathy is thought to be a key factor of COVID-19-associated coagulopathy, markers indicative of this process that are prognostic of disease severity have not been well-established in this patient population. Using plasma profiling of patients with COVID-19, we identified circulating markers that segregated with disease severity: markers of angiogenesis (VEGF-A, PDGF-AA and PDGF-AB/BB) were elevated in hospitalized patients with non-critical COVID-19 infection, while markers of endothelial injury (angiopoietin-2, FLT-3L, PAI-1) were elevated in patients with critical COVID-19 infection. In survival analysis, elevated markers of endothelial injury (angiopoietin-2, follistatin, PAI-1) were strongly predictive of in-hospital mortality. Our findings demonstrate that non-critical and critical phases of COVID-19 disease may be driven by distinct mechanisms involving key aspects of endothelial cell function, and identify drivers of COVID-19 pathogenesis and potential targets for future therapies.